The Influence of Information Types and Search Intention in Using Branded Or Generic Search Query - Ave Pinem; Putu Wuri Handayani; Clarissa Martalin Winona (Jurnal Sistem Informasi, 2023)
This study aims to analyze the effect of each type of information and search intention on the use of branded or generic search queries on search engines. This is done because of the emergence of the phenomenon of information overload or explosion of information. The types of tourism information studied are transportation, accommodation, restaurants, shopping places, and tourist attractions with two types of intention, namely purchase intention and intention to search. This study used a quantitative approach by distributing online questionnaires to users who had searched using a search engine and managed to collect 1,256 respondents. Data were analyzed using binary logistic regression. We found that intention influences the use of branded or generic search queries and several types of information influence the use of search queries. Transportation and shopping information could influence users in choosing to use generic or branded search queries.